Enhancing healthy ecosystems in northern Ghana through eco‑friendly farm‑based practices: insights from irrigation scheme‑types - Agula, C.; Mabe, F.N.; Akudugu, M.A.; Dittoh, S.; Ayambila, S.N. (BMC Ecology, 2019)
Background: Farming practices vary from farmer to farmer and from place to place depending on a number of factors including the agroclimatic condition, infrastructure (e.g. irrigation facilities) and management mechanisms (private versus state management). These together affect the functioning and sustainability of the ecosystems. For the sustainability of ecosystems, farmers need to employ ecosystem-based farm practices. This paper examines the ecosystem-based farm management practices (EBFMPs) in private and state-managed irrigation schemes. It also analyses the drivers of farmers’ willingness to pay for EBFMPs sustainability. The study employed mixed methods design, using both qualitative and quantitative techniques of data collection through key informant interviews, focus group discussions and semi-structured questionnaires administered to 300 households. The various EBFMPs adopted by farmers were examined and descriptively presented. The Chi-square automatic interaction detector (CHAID) and multiple linear regression were used to assess the predictors of farmers’ willingness to pay for EBFMPs to enhance the health of agroecosystems. Compost application, conservative tilling, conservation of vegetation, mulching, crop rotation, intercropping with legumes, efficient drainage systems and bunding were the EBFMPs captured in this paper. Results: Farmers in privately-managed irrigation schemes (PIS) more often apply EBFMPs compared with those in state-managed irrigation schemes (SIS). The paper also found that farmers’ willingness to pay to sustain EBFMPs for healthy ecosystems is significantly determined by the type of irrigation scheme they cultivate in (that is, PIS or SIS), their level of education, marital status and perception of soil fertility. Conclusions: Policy makers, implementers, and other stakeholders need to consider the capacity building of irrigation farmers, especially those in SIS in northern Ghana by educating them on agricultural production and ecosystem nexus to enhance the level of usage and willingness to pay for EBFMPs sustainability.
Research Article
Keywords: Farm management practices; Agroecosystems; Contingent Valuation Method; Chi-square automatic interaction detector